Products and Provinces : A Disaggregated Panel Analysis of Canada's Manufacturing Exports - Agur, Itai (IMF Working Papers; Working Paper ;, 2016)
The waning of the commodity boom places renewed emphasis on manufacturing as an engine for Canadian growth. However, Canadian manufacturing exports have been relatively stagnant since 2000. While the exchange rate depreciation over the past two years has energized export growth, the response has not been as strong as would have been expected given the size of the depreciation. More fundamental issues appear to be impeding the growth of the Canadian manufacturing sector. This study analyzes the structural factors behind export competitiveness by using unique Canadian data on exports, which are disaggregated both by province and by product. Matching exports to similarly disaggregated data on R and D, the capital stock and other supply-side variables, we find that these variables significantly affect export growth, beyond the impact of the exchange rate. In particular, investment in R and D, capital infrastructure and vocational training improves innovation and production capacity. These results are robust to a factor-augmented approach that controls for multicollinearity.